Effect of breeding during the peri-vaccination window against foot-and-mouth disease on the pregnancy rate in the cow: A retrospective study - PATEL, B H MANJUNATHA; RAINA, AAMIR AHMAD; JEYAKUMAR, SAKTHIVEL; SELVAN, R PTAMIL; GOWANE, G R; KRISHNASWAMY, NARAYANAN; DECHAMMA, H J; VIJAYAPILLAI, UMAPATHI; SOMAGOND, ARUN; SANYAL, ANIKET; GAUR, GYANENDRA KUMAR; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2023)
As emerging evidence indicates that FMD vaccination causes variable degrees of pregnancy loss in the beef cow, the study was conducted at NDRI SRS in sub-tropical conditions in the year 2021 to investigate its effects on the pregnancy rate in the dairy cow when they were bred within 14 days of FMD vaccination. Retrospective data on AI done within 14 days post FMD vaccination (dpv -14 to +14) and the corresponding pregnancy outcome were collected for 6 years (January 2016 to January 2021) and each record was categorized into AI pre-vaccination (dpv -14 to -1) or AI post-vaccination (dpv 0 to 14). After excluding repeat breeding cows and pregnant heifers, the final dataset consisted of 47 records derived from crossbred and Deoni cows. The binary outcome variable pregnancy was regressed on the categorical predictor variables such as day of AI with respect to dpv 0, stage of lactation and parity. The results indicated that the odds of pregnancy in the AI post-vaccinated group was 0.47 (95% confidence interval: 0.10-1.88) value) as compared with AI pre-vaccinated group. It can be concluded that FMD vaccination has no significant effect on pregnancy outcome if the animals are bred 14 days before and 14 days after FMD vaccination (irrespective of breed, age, parity, days in milk).